2006
DOI: 10.1016/j.adolescence.2006.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and parenthood among young people in and leaving care: what are the influencing factors, and what makes a difference in providing support?

Abstract: Previous research has shown increased vulnerability to teenage parenthood for young people with experience of local authority care. This study explored factors contributing to early pregnancy and parenthood among young people in and leaving care; the types of support available; and the extent to which services are perceived as accessible. Semi-structured interviews were undertaken with 63 young people. The study findings suggest that young people's experiences both prior to, and during care, influence their de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 11 publications
1
55
0
Order By: Relevance
“…The retrospective accounts of the care-leaver participants indicate that they were well aware that information was, or could be shared and this compromised their sense of privacy and was a source of concern for YPISC. Other studies have also reported the concerns of YPISC about confidentiality in relation to their sexual health (Billings et al, 2007;Chase et al, 2006). Compared to previous studies (Billings et al, 2007;Chase et al, 2006), however, ours provides far more empirical examples and offers an analysis of the impact on the young people of information-sharing between professionals that has not featured in existing studies.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The retrospective accounts of the care-leaver participants indicate that they were well aware that information was, or could be shared and this compromised their sense of privacy and was a source of concern for YPISC. Other studies have also reported the concerns of YPISC about confidentiality in relation to their sexual health (Billings et al, 2007;Chase et al, 2006). Compared to previous studies (Billings et al, 2007;Chase et al, 2006), however, ours provides far more empirical examples and offers an analysis of the impact on the young people of information-sharing between professionals that has not featured in existing studies.…”
Section: Discussionmentioning
confidence: 67%
“…The importance of confidentiality has also emerged in a small number of empirical studies focusing on the sexual health of YPISC in Britain (McFeely, 2005;Billings, Hashem, & Macvarish, 2007;Chase, Maxwell, Knight, & Aggleton, 2006) and the USA (Constantine, Jerman, & Constantine, 2009). Billings and colleagues (2007), based on six focus groups with twenty 15-20 year-old YPISC and care-leavers found that participants linked trust to confidentiality when discussing healthcare interactions, and revealed fear that confidentiality would be breached, generating a distrust in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Although these aspects may accrue to youth both with and without foster care histories, young mothers with foster care backgrounds have indicated early parenting may help to alleviate feelings of inadequacy and offer a new sense of belonging . In a study of young British parents who aged out of foster care, participants shared that becoming a parent helped lessen feelings of loneliness, rejection, and abandonment (Chase, Maxwell, Knight, & Aggleton, 2006;Knight et al, 2006). Parents also reported finding security, stability, and a sense of accomplishment in becoming a parent.…”
Section: Intangible Resources: Adult Identity and Negotiating The Pasmentioning
confidence: 99%
“…The children of mothers who have been looked after may themselves be taken into care and, because of this, some young women avoid involvement with services. 147 Botchway and colleagues 148 analysed data from the UK Millennium Cohort Study on pregnancy-related outcomes in women who had spent a period of time in care. The study focused specifically on the extent to which these women differed from those with no experience of care, in relation to factors considered important to the health and well-being of infants, namely smoking during pregnancy, symptoms of maternal depression and initiation of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%